Prevalence and risk factors associated with Peste des Petits Ruminant (PPR) in Jashore, Bangladesh: Prevalence and risk factors associated with PPR in goat - Ashing Yaing Marma; Sohan Kabir; Arnab Kumer Sutra Dhar; Muhtadi Md Waliullah; Sajeda Sultana (Research in Agriculture Livestock and Fisheries, 2025)
The FAO and the WOAH are launching a global effort to eradicate Peste des Petits Ruminants (PPR) which causes high morbidity and mortality in small ruminants. PPR is the number one killer disease of goats in Bangladesh. The objective of the study was to determine the prevalence and risk factors associated with PPR in goats in Sharsha, Jashore, from September 2023 to November 2023. Clinically infected 456 goats were examined during this period. The presumptive diagnosis of the PPR diseases was based on the owner’s complaints, clinical history, signs and symptoms, and physical examinations of goats. Statistical analysis was done by Chi-square test, and the P-value was calculated by using SPSS 22 (SPSS, Inc., Chicago, IL). In this study, 97 goats (21.3%) were found to be PPR infected out of 456 visited goats in Upazila Veterinary Hospital. PPR was more observed and significantly more prevalent (<0.001) in Black Bengal goats (76.2 %) followed by 13.4% crossbreeds, 8.2% Jamunapari and 2.0% Beetal goats. The prevalence of PPR is not statistically significant according to sex but highly significant (P<0.001) in un-vaccinated (76.29%) goats and worm-infested goats (79.38%). Age and rearing system were also significant factors (P<0.001) in the prevalence of PPR of goats. 6-24-month-old goats (54.64%) were more susceptible than adults (8.25%) and household-rearing-system goats (70.10%) were more susceptible than intensive-system goats (6.19%) to PPR. These results of the study may be useful in creating a control and eradication program of PPR in Sharsha, Jashore. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 15-23